2015
DOI: 10.1016/j.molp.2015.03.011
|View full text |Cite
|
Sign up to set email alerts
|

High REDOX RESPONSIVE TRANSCRIPTION FACTOR1 Levels Result in Accumulation of Reactive Oxygen Species in Arabidopsis thaliana Shoots and Roots

Abstract: Redox Responsive Transcription Factor1 (RRTF1) in Arabidopsis is rapidly and transiently upregulated by H2O2, as well as biotic- and abiotic-induced redox signals. RRTF1 is highly conserved in angiosperms, but its physiological role remains elusive. Here we show that inactivation of RRTF1 restricts and overexpression promotes reactive oxygen species (ROS) accumulation in response to stress. Transgenic lines overexpressing RRTF1 are impaired in root and shoot development, light sensitive, and susceptible to Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 86 publications
7
77
0
Order By: Relevance
“…A recent study demonstrated that REDOX RE-SPONSIVE TRANSCRIPTION FACTOR1 (RRTF1) might function as a key regulator of systemic ROSdependent responses during high light stress (Matsuo et al, 2015). RRTF1-dependent systemic signaling was shown to be regulated by WRKY transcription factors (Matsuo et al, 2015), whose expression is enhanced during RBOHD-dependent SAA (Miller et al, 2009), but its rate of systemic response is slower than that of the ROS wave.…”
Section: The Ros Wave Retrograde Signaling and Transcriptional Regumentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that REDOX RE-SPONSIVE TRANSCRIPTION FACTOR1 (RRTF1) might function as a key regulator of systemic ROSdependent responses during high light stress (Matsuo et al, 2015). RRTF1-dependent systemic signaling was shown to be regulated by WRKY transcription factors (Matsuo et al, 2015), whose expression is enhanced during RBOHD-dependent SAA (Miller et al, 2009), but its rate of systemic response is slower than that of the ROS wave.…”
Section: The Ros Wave Retrograde Signaling and Transcriptional Regumentioning
confidence: 99%
“…RRTF1-dependent systemic signaling was shown to be regulated by WRKY transcription factors (Matsuo et al, 2015), whose expression is enhanced during RBOHD-dependent SAA (Miller et al, 2009), but its rate of systemic response is slower than that of the ROS wave. RRTF1 could therefore play a role in the regulation of gene expression downstream to the ROS wave during SAA (Fig.…”
Section: The Ros Wave Retrograde Signaling and Transcriptional Regumentioning
confidence: 99%
“…Total RNA from roots of transgenic A. thaliana (Col-0) expressing cytosolic apoaequorin 729 (pMAQ2, Knight et al, 1991, Polisensky andBraam, 1996) procedure and determination of the ABA concentrations were performed as described in 775 Matsuo et al (2015). Stomata closure was determined as described in Vahabi et al (2016).…”
mentioning
confidence: 99%
“…Several members of the FAR-RED-IMPAIRED RESPONSE1-related sequence family of transcription factors were also recently implicated in integrating ROS with different developmental and environmental responses (Wang and Wang, 2015). Additional ROS-response regulatory proteins identified in recent years include the APETALA2/ethylene response transcription factor REDOX RESPONSIVE TRANSCRIP-TION FACTOR1 that is regulated by different WRKYs (Matsuo et al, 2015), different members of the NAC family of transcription factors (e.g. Fang et al, 2015;Chen et al, 2016;Zhu et al, 2016), and different zinc-finger proteins such OXIDATIVE STRESS2 (He et al, 2016).…”
mentioning
confidence: 99%